Critical values in Hematology. (2nd April 2014) - McFarlane, A.; Aslan, B.; Raby, A.; Bourner, G.; Padmore, R.
Summary Introduction Critical values are life‐threatening results that require immediate notification to the patient's healthcare provider. Accreditation bodies require laboratories to establish critical values. A survey of Ontario laboratories was conducted to determine current practice for critical values in hematology. Methods The survey was sent to 182 participants questioning sources for establishing critical values, levels, review frequency, delta checks, and reporting. The survey was completed by laboratory managers, supervisors, technical specialists, senior technologists, and bench technologists working in hematology. Results The majority of participating laboratories have established critical values limits for hemoglobin, leukocyte counts, and platelet counts. Most laboratories also include the presence of malaria parasites and blast cells. Some laboratories reported the presence of plasma cells, sickle cells, schistocytes, and spherocytes as critical values. Multiple sources are used for establishing a critical value policy. There was variability for the frequency of critical values review. Rules may differ for a first‐time patient sample vs. a repeat patient sample. Delta checks are seldom used to determine whether a result should be called a critical value. Most participants require the individual taking the critical result(s) to read back and confirm that they are directly involved with the patient's care. Conclusion There is a lack of consensus for critical values reporting in hematology. As critical value reporting is crucial for patient safety, standardization of this practice would be beneficial.